Effects of negativity bias on amygdala and anterior cingulate cortex activity in short and long emotional stimulation paradigms. Issue 6 (7th April 2021) - Yoshida, Nobukiyo; Kotani, Yasunori; Ohgami, Yoshimi; Kunimatsu, Akira; Inoue, Yusuke; Kiryu, Shigeru; Okada, Yukinori
Abstract : Recent functional studies have reported that amygdala and anterior cingulate cortex (ACC) dysfunction is a reproducible and good biomarker of major depressive disorder. When we use the activation of these regions as biomarkers of major depressive disorder, a short and simple stimulation paradigm could be preferable to reduce the burden on patients. However, negativity bias, which is the phenomenon by which negative stimuli are processed noticeably faster than positive stimuli, might affect the activation of these regions in the short and simple stimulation paradigm. Few studies have reported the relationship between the length of the stimulation paradigm and activation in the amygdala and ACC from the viewpoint of negativity bias. The purpose of this study was to assess the effects of negativity bias on the amygdala and ACC as a result of manipulating the stimulation paradigm (short-simple vs. long-complex conditions) on presenting pleasant and unpleasant pictures. Image analyses showed that the amygdala was activated during unpleasant picture presentation, regardless of the task length, but no activation was observed during pleasant picture presentation under the short-simple condition. The ACC was deactivated in both the short-simple and long-complex conditions. Region of interest analyses showed that the effect of negativity bias was prominent for the amygdala in the short-simple condition and for the ACC in the long-complex condition. In conclusion, the effects of negativity bias depend on neural regions, including the amygdala and ACC, and therefore, we should consider these effects while designing stimulation paradigms.